1998
DOI: 10.2331/fishsci.64.148
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ca<sup>2+</sup> Concentration around Myofibrillar Mg<sup>2+</sup>-ATPase on the Speed and Pattern of Rigor Mortis in Fish Species or Cultured and Wild Fish

Abstract: The influence of Ca2+ concentration around myofibrillar Mg2+-ATPase on the speed and pattern of rigor mortis in fish species or cultured and wild fish was studied. The change of contraction in pillar form muscle with the lapse of storage time reflected very well the temporal change of gram of tension in muscle of cultured red sea bream. This result showed that the contractile percentage of muscle is very useful on the progress of rigor mortis. The progress of muscular contraction differed among fish species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The change of muscle length accompanying caffeine contraction was measured with the lapse of time, and was expressed as the contractile percentage of muscle. 14 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The change of muscle length accompanying caffeine contraction was measured with the lapse of time, and was expressed as the contractile percentage of muscle. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have attributed the differences in rigor mortis progress of fish to several causes such as: the resolution speed of total ATP and the accumulation of lactic acid, 3–13 myofibrillar Mg 2+ ‐ATPase activity, 4,13–16 and Ca 2+ uptake by sarcoplasmic reticulum(SR). 4,16 Regarding the difference between cultured and wild red sea bream, we reported that the rigor mortis progress reached the maximum level earlier in cultured fish than in wild fish, and the muscular contractile percentage was also higher in cultured fish than in wild fish.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fish bodies of both fish sample species differed from specimens in our previous papers ( Table 1). 4,8,9 The 2‐year‐old fish had been cultivated at Toisu Bay, Nagasaki prefecture, and were purchased from a fish farmer in the summer with an ambient temperature of ~25°C. The fish were held in a laboratory water tank at an ambient temperature of 25°C for more than 2 months, and adequately fed the same moist pellets as the farm, before being used as experimental sample fish.…”
Section: Methodsmentioning
confidence: 99%